Influence of age and sex on the diagnostic accuracy of pleural fluid carcinoembryonic antigen for malignant pleural effusion: a post hoc analysis - Yang, Dan-Ni; Wen, Jian-Xun; Niu, Yan; Hai, Ling; Yang, Qian; Cha, Su-Na; Yan, Cheng; Zhu, Hong-Zhe; Jiang, Ting-Wang; Yan, Li; Huang, Jin-Hong; Chen, Hong; et al. (Frontiers in Oncology, 2025)
IntroductionThe diagnostic value of pleural fluid carcinoembryonic antigen (CEA) for malignant pleural effusion (MPE) has been well recognized. However, whether age and sex affect its diagnostic accuracy remains unknown. This study aimed to investigate the influence of age and sex on the accuracy of CEA for differentiating MPE and benign pleural effusion (BPE).MethodsWe enrolled participants from a prospective cohort (SIMPLE) and a retrospective cohort (BUFF). All participants were patients with pleural effusion with undetermined causes. The clinical characteristics were extracted from the medical records of participants. The area under receiver operating characteristics (ROC) curve (AUC) was used to estimate the diagnostic accuracy of CEA. The effects of sex and age on the diagnostic accuracy of CEA for MPE were analyzed using subgroup analysis. A method characterized by resampling participants with different upper limits was also used to investigate the effect of age.ResultsThe SIMPLE cohort included 210 participants (91 patients with MPE and 119 patients with BPE), and the BUFF cohort included 235 participants (50 patients with MPE and 185 patients with BPE). Sex did not significantly affect the diagnostic accuracy of CEA. Subgroup analyses with both cohorts revealed the decreased AUC in older patients. The resampling method revealed decreased AUC with the advancement of age.ConclusionsAge should be considered when interpreting the diagnostic accuracy of pleural fluid CEA for MPE, while the effects of sex can be ignored.